Advances in industrial and environmental microbiology - Vaz-Moreira, Ivone (Switzerland : MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The development of civilization entails the need to find new technological solutions leading to products with new properties. Allies in these efforts are microorganisms that have developed skills to synthesize products with properties of interest to the industry, environmental remediation or water treatment. The evolution of the omics approaches brought new tools to explore the microbial diversity and microorganisms' potential. These new methodological approaches are readily used in both industrial and environmental microbiology.
Advances in Industrial and Environmental Microbiology -- A Review on the Importance of Microbial Biopolymers Such as Xanthan Gum to Improve Soil Properties -- Effect of Aeration Mode on Microbial Structure and Efficiency of Treatment of TSS-Rich Wastewater from Meat Processing -- Microbial Activity in Subterranean Ecosystems: Recent Advances -- Occurrence of Fluoroquinolones and Sulfonamides Resistance Genes in Wastewater and Sludge at Different Stages of Wastewater Treatment: A Preliminary Case Study -- Composition Characteristics of Organic Matter and Bacterial Communities under the Alternanthera philoxeroide Invasion in Wetlands.
Includes bibliographical references.
Keywords: MICROBIAL ECOLOGY